1994
DOI: 10.1002/cne.903480402
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic projection from the basal forebrain to the visual sector of the thalamic reticular nucleus in the cat

Abstract: We examined the projection from the basal forebrain to thalamic and cortical regions of the visual system in cats, with particular reference to the visual sector of the thalamic reticular nucleus, the lateral geniculate nucleus, and the striate cortex. First, we made injections of wheat germ agglutinin conjugated to horseradish peroxidase (WGA-HRP) into the visual sector of the thalamic reticular nucleus and found cells labeled by retrograde transport in the lateral nucleus basalis magnocellularis. Injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 91 publications
4
59
0
Order By: Relevance
“…The ChAT antibody specifically binds a protein with a molecular weight of 68 kDa that forms 153 mol acetylcholine/minute/mg (Eckenstein and Thoenen, 1982). In cat tissue, this antibody stains the same pattern of thalamic terminals, and basal forebrain and mesopontine tegmentum cells, as has been demonstrated with other cholinergic markers in a variety of species Bickford et al, 1993Bickford et al, , 1994.…”
Section: Antibody Characterizationmentioning
confidence: 71%
See 1 more Smart Citation
“…The ChAT antibody specifically binds a protein with a molecular weight of 68 kDa that forms 153 mol acetylcholine/minute/mg (Eckenstein and Thoenen, 1982). In cat tissue, this antibody stains the same pattern of thalamic terminals, and basal forebrain and mesopontine tegmentum cells, as has been demonstrated with other cholinergic markers in a variety of species Bickford et al, 1993Bickford et al, , 1994.…”
Section: Antibody Characterizationmentioning
confidence: 71%
“…Thus, it can be concluded that all corticogeniculate terminals are smaller than RLD profiles. Furthermore, all other inputs to the dLGN and PGN either are smaller than RLD profiles or contain distinct neurotransmitters (Fitzpatrick et al, 1984Montero, 1986;Raczkowski and Fitzpatrick, 1989;Bickford et al, 1993Bickford et al, , 1994Erisir et al, 1997;Wang et al, 2001Wang et al, , 2002a. Therefore, all available evidence indicates that RLD profiles originate from the collaterals of geniculocortical axons.…”
mentioning
confidence: 91%
“…GABAergic inputs to RTN cells derive from at least two sources. GABAergic projection cells located in the basal forebrain and the pars reticulata of the substantia nigra (Jourdain et al, 1989;Asanuma and Porter, 1990;Paré et al, 1990;Bickford et al, 1993Bickford et al, , 1994 send axons to end on proximal dendrites of RTN cells (Asanuma, 1994). Another source of GABAergic inputs is from neighboring RTN cells via axon collaterals and in some species from dendritic processes (Deschênes et al, 1985; Yen et al, 1985).…”
Section: Functional Implications Of Synaptic Inputs On Single Rtn Cellsmentioning
confidence: 96%
“…For this, we followed our previously described protocol (Bickford et al, 1994;Erişir et al, 1997a), modified from Phend et al (1992). Briefly, all solutions except the primary and secondary antibodies were filtered through a 0.22-µm Millipore filter.…”
Section: Postembedding Immunogoldmentioning
confidence: 99%
“…Finally, the sections were rinsed in TBST at pH 7.6 and deionized water, placed in 2% glutaraldehyde (EM grade) for 10 minutes, rinsed again in deionized water, and counterstained with uranyl acetate and lead citrate to increase contrast. We used our previously described method (Bickford et al, 1994;Erişir et al, 1997a) for distinguishing significant postembedding levels from background labeling. The control for GABA labeling background were excitatory terminals of extraretinal origin, known as ''RD'' terminals.…”
Section: Postembedding Immunogoldmentioning
confidence: 99%